1997
DOI: 10.1021/bi962624g
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Associated c-type Cytochromes from the Green Sulfur Bacterium Chlorobium limicola forma thiosulfatophilum:  Purification and Characterization of Cytochrome c553

Abstract: Tetraheme cytochromes involved in photosynthetic electron transport have previously been described associated with the reaction centers of purple photosynthetic bacteria; however, similar heme proteins have not until now been characterized in the phylogenetically distinct green sulfur bacteria. In this paper we describe the first isolation and characterization of a multitheme, membrane-associated cytochrome from a green sulfur bacterium, Chlorobium limicola forma thiosulfatophilum. We show that this cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Chlorobium limicola forma thiosulfatophilum strain tassajara (kindly provided by N. Pfennig, Constance, Federal Republic of Germany) was grown, and membrane fragments were isolated as described previously (1). For oriented membrane multilayers, membrane fragments from C. limicola were separated from chlorosomes by the method of Schmidt (31).…”
mentioning
confidence: 99%
“…Chlorobium limicola forma thiosulfatophilum strain tassajara (kindly provided by N. Pfennig, Constance, Federal Republic of Germany) was grown, and membrane fragments were isolated as described previously (1). For oriented membrane multilayers, membrane fragments from C. limicola were separated from chlorosomes by the method of Schmidt (31).…”
mentioning
confidence: 99%
“…4). A previous study has shown that cytochromes c and b have two peaks between 550 nm and 560 nm, when absorption was measured at ultralow temperature [40]. It is likely that the plateau we observed in wild type is composed of two peaks of cytochromes c and b, but the peaks were not resolved at the room temperature we used for the measurement.The complement strain (C0531) and 015F07 had a wide peak similar to wild type with the maximum absorption at 558 nm and 556 nm, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…Characteristic of the porphyrin compounds Soret band is the peak absorption at ~420 nm [39]. In addition, the wild type strain (8004) showed a peak plateau at absorption from 553.5 nm to 564 nm, while the mutant (0531pk) had only one peak at the absorption of 564 nm, which is typical of b-type cytochromes [40] (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…These halves are therefore tentatively referred to as ''N-c z '' and ''C-c z ,'' respectively. Other sequence data were obtained from the JGI microbial genomic database and the GenBank database b Photosynth Res (2010) 104: 189-199 193 resonance (ESR) spectroscopic method, but its function is still unknown (Albouy et al 1997).…”
Section: Ctepidum Cz-sol -F D F D a A K K L V D V R --C N K C H T L mentioning
confidence: 99%